Problemas dos pacientes em pós-operatório de cirurgia cardíaca, na unidade de terapia intensiva: intervenção de enfermagem - Pagliuca, Lorita Marlena Freitag (1986)
The present report is an experimental study in which the influence of an orientation model, aplicated in the preoperatory, upon the manifestation of patient.es problems in heart surgery posoperatory at Intensive Care Unit Í.ICUI, was s.tudied, The orientation model was elaborated based in the previous Rnowledge one had about those. problems that most bother the patients at ICLJ, and it was applied at three experimental groups, in two of them by the researcher and in the. ather one by the institutian nurses. The second experimental group was assisted by the researcher at ICU and the nurses of the Medical-Surgical Nursing Habilitation Course, using C24 T the Nursing Process proposed by HORTA < The experimental groups were. consisted by- 5.(1 patients each and the results were compared uritEL those: of the contrai groups, made of 104 pacients. The results that were fo.und permitted to conclud the problems manifestation or not between the. experimental and control groups were not significants; about the. kind of problem manifested, on the Intuhation Tuba problem there was na significant difference between control and experimental group;. • about the Amb.ient problem it was significant higher the.r incidence of problems ■ 'in the control group than in the experimental one; the Respiratory Assistence problem did not present significance between the: groups; the Dorsal Rosition problem was significant higher in the control group than in the experimental group; the Rain problem did not present significance between the studied groups; about Dther problem manifestation,the number was significative, higher in the experimental group than in the. control. There was a worh. hypothesis that the patients submitted to preoperatory orientation would present modifications on the problems manifestation, The hypothesis- was accepted for Ambient and Dorsal Position problems, because its manifestations were significant lower in the orientpted groups, and was refused for problems manifestation or not and for Intubation Tube, Respiratory Assistence, Pain, Complain against Nursing and Other Problems. The report still comprehend an exploratory study of Nursing Process at ICU aplication with nursing students and permitted to determine the humans needs, often afected in the patient at heart surgery posope.ratory at ICU. The neceasíties are therapeutic, * circulation, hydroeletrolitic balance, basic-accid balance, body care, oxigenation, mucous^cutaneous integrity, urinary elimination neurologic regulation, security, pain perception, rest and sleep, motility, physical; integrity, nutrition, thermic regulation, hormoníc regulation and immunological regulation.